20 years of research on Information Literacy in Brazil: thematic analysis of the theses and dissertations in the CAPES Catalog of Postgraduate Programs. - Farias, Gabriela Belmont de; Mata, Marta Leandro da; Meneses Alves, Ana Paula; Santos, Camila Araujo dos [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2021)
This paper presents an overview of the 20 years of research on Information Literacy, through the analysis of the themes addressed in the research developed in the Graduate Programs in Information Science in Brazil. The scope of the research consisted of identifying the thematic perspectives and the transversality of Information Literacy in the Brazilian scientific production of the last 20 years, considering as reference the first research published in the year 2000. For the selection of the theses and dissertations, the Catalog was used of Theses and Dissertations from the Coordenacao de Aperfeicoannento de Pessoal de Nivel Superior (CAPES), delimiting the period referring to the years 2000-2019. The research is of an exploratory-type quali-quantitative nature. To compile and analyze the results, the content analysis technique was used, in which the indicators proposed by Belluzzo (2017) were used as a category for analyzing the content of each research. The results show that most publications are focused on the Master's theme. An increase in scientific production on the subject was observed from the year 2011, with a peak in the year 2016. The five Higher Education Institutions that gather the most public works on Colnfo are the University of Brasilia, the Federal University of Minas Gerais, Sao Paulo State University Marilia, Federal University of Bahia and Federal University of Santa Catarina. Scientific production on the subject is still very much centered in the Information Science area and with a large flow of productions in the south-central region of Brazil. We highlight that the professors / researchers who provided the most guidance on the topic have between 08 and 11 oriented works. With regard to the themes, the transversality of the themes stands out, especially with the area of Education.
Keywords: Information Literacy; Information Science; Thematic Indicator; Graduate Program